2022
DOI: 10.3390/biomedicines10020390
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta Spectrum Disorder Complicated with Endometriosis: Systematic Review and Meta-Analysis

Abstract: This study aimed to assess the relationship between placenta accreta spectrum disorder (PASD) and endometriosis. The relationships among pregnancy, assisted reproductive technology (ART), placenta previa, ART-conceived pregnancy and PASD were also determined. A systematic literature review was conducted using multiple computerized databases. Forty-eight studies (1990–2021) met the inclusion criteria. According to the adjusted pooled analysis (n = 3), endometriosis was associated with an increased prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 113 publications
(340 reference statements)
1
13
0
Order By: Relevance
“…Our study found that women with VCI were more likely to have a placenta previa than those without. A previous meta-analysis reported that ART pregnancies were associated with a higher rate of placenta previa than non-ART pregnancies (OR 2.96, 95%CI 2.43–3.60) [ 11 ]. Nevertheless, only one study showed a significantly higher incidence of low-lying placenta in ART pregnancy compared to that in non-ART pregnancy (adjusted OR 1.83, 95%CI 1.04–3.12) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study found that women with VCI were more likely to have a placenta previa than those without. A previous meta-analysis reported that ART pregnancies were associated with a higher rate of placenta previa than non-ART pregnancies (OR 2.96, 95%CI 2.43–3.60) [ 11 ]. Nevertheless, only one study showed a significantly higher incidence of low-lying placenta in ART pregnancy compared to that in non-ART pregnancy (adjusted OR 1.83, 95%CI 1.04–3.12) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ART is associated with an increased prevalence of some placental disorders, such as placenta previa and placenta accreta spectrum disorder (PASD). Interestingly, recent systematic reviews have found that the risk of placenta previa and PASD is different among ART types [ 11 ]. For instance, a frozen embryo transfer is associated with a higher incidence of PASD than a fresh embryo transfer [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we reviewed the literature for similar cases. According to the 2020 edition of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement [ 21 ], we conducted a systematic literature search in the PubMed and Google scholar databases (first 100 hits) from their inception to 31 January 2022, as previously performed with modification [ 22 , 23 , 24 ]. The keywords “inguinal lymph node” or “groin lymph node” and “fallopian tube carcinoma,” “ovarian carcinoma,” or “primary peritoneal carcinoma” were used to search.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our systematic review, clinicians should consider the possibility of endometriosis in pregnant women. Since a diagnosis of endometriosis during pregnancy is challenging [ 62 ], a medical consultation would be helpful to determine whether endometriosis is present or whether there has been any past surgical history of endometriosis prior to pregnancy.…”
Section: Discussionmentioning
confidence: 99%